Perception of TB BTA (+) Patients about Treatment with Healing Status - Purwaningsih Purwaningsih; Hanik Endang Nihayati; Khikmatul Mu’jizah (Jurnal Ners, 2009)
Introduction: Tuberculosis (Tb) is infection disease that remains a major global public-health problem. Although it is curable and preventable, Tb remains a major cause of morbidity and mortality. Wrong perception about TB and treatment often make non-adherence to treatment regimen. This study was aimed to analyze the correlation between perception of Tb BTA (+) patients about treatment with healing status. Method: This research used cross sectional-retrospective design. The sample were 23 Tb BTA (+). The independent variable was perception of Tb BTA (+) patients about treatment and dependent variable was healing status. The data were analyzed by Kolmogorov-Smirnov test with significance α≤ 0.05. Result: The result showed that perception of Tb BTA (+) patients about treatment did not has significance level with healing status (p=1,00). It can be concluded that perception of Tb BTA (+) patients about treatment did not has correlation with healing status. Discussion: It is recommended to the Turen public health center about TB programme to include health education for TB patients and family regularly in addition to increase patients adherence.